2020
DOI: 10.1186/s12889-020-09748-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence across time and space of drug- and cannabinoid- exposure and adverse mental health outcomes in the National Survey of Drug Use and Health: combined geotemporospatial and causal inference analysis

Abstract: Background: Whilst many studies have linked increased drug and cannabis exposure to adverse mental health (MH) outcomes their effects on whole populations and geotemporospatial relationships are not well understood. Methods Ecological cohort study of National Survey of Drug Use and Health (NSDUH) geographically-linked substate-shapefiles 2010–2012 and 2014–2016 supplemented by five-year US American Community Survey. Drugs: cigarettes, alcohol abuse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 85 publications
1
18
0
1
Order By: Relevance
“…Moreover, CUD-documented patients were over three times as likely as CU patients to have schizophrenia/psychotic disorders, and over twice as likely to have depression or anxiety diagnoses. These findings support the extensive body of research demonstrating a correlation between cannabis use and mental health problems [ 8 , 11 , 16 , 41 44 ] and the association between cannabis use documentation and the presence of psychiatric diagnoses in EHRs [ 15 , 17 ]. They also underscore the importance of screening and assessment for co-occurring mental health disorders among people who use cannabis or have cannabis use disorders, and ensuring that they receive evidence-based psychosocial and pharmacological interventions as needed [ 45 – 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, CUD-documented patients were over three times as likely as CU patients to have schizophrenia/psychotic disorders, and over twice as likely to have depression or anxiety diagnoses. These findings support the extensive body of research demonstrating a correlation between cannabis use and mental health problems [ 8 , 11 , 16 , 41 44 ] and the association between cannabis use documentation and the presence of psychiatric diagnoses in EHRs [ 15 , 17 ]. They also underscore the importance of screening and assessment for co-occurring mental health disorders among people who use cannabis or have cannabis use disorders, and ensuring that they receive evidence-based psychosocial and pharmacological interventions as needed [ 45 – 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…Cannabinoid genotoxicity can be expected to manifest in public health in the clinical domains of congenital anomalies and cancer epidemiology. Combining recent multi-jurisdictional congenital anomaly data from Colorado, Hawaii, Canada, Australia and the USA [ 64 , 103–105 , 157 , 167 , 168 ] with the present report and previous testicular and paediatric cancer reports [ 12–15 , 18 , 21 , 33 , 34 , 36 , 38 , 39 ], together with well-documented negative impacts on mental health [ 66 ] and paediatric autism rates [ 62 , 63 , 100 ], the conclusion that widespread cannabis genotoxicity and neurotoxicity as implicit in cannabis-liberal paradigms constitute an impending public health disaster of catastrophic proportions seems inescapable. Further historical and time-projected health econometric quantitative studies across these wide domains of clinical pathology are indicated.…”
Section: Discussionmentioning
confidence: 90%
“…In short the well described implication of cannabis with heritable clinical genotoxic syndromes is a major motivation for carefully controlling the community penetration of cannabinoid products of all types in line with the way known genotoxins are handled, addressed and carefully controlled in every other entry in the pharmacopeia of western medicine. This statement in relation to cannabinoid genotoxicity is strongly supported by the now known causal links relating to cannabinoid neurotoxicity both in the exposed, expressed as high rates of mental illness in young American adults [ 97 ], and in their offspring, expressed as high and rapidly increasing rates of child autism across USA [ 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 86%